A new species of Salamander (Caudata, Plethodontidae, Bolitoglossa) from Serranía de los Yariguíes, Colombia - Meza-Joya, Fabio Leonardo; Hernández-Jaimes, Carlos; Ramos-Pallares, Eliana (Zootaxa, 2017)
A new species of Bolitoglossa (Plethodontidae) is described from Andean cloud forests on the western slope of Serranía de los Yariguíes in the Cordillera Oriental of Colombia. This new species is distinguished from all other species of the Bolitoglossa adspersa species group by differences in adult body size, morphometric proportions, and tooth counts. The validity of the new species is also supported by molecular analyses. This new species increases the number of salamander species in Colombia to 23 and highlights the Cordillera Oriental of Colombia, with 11 species, as the region with the highest diversity of Bolitoglossa in South America.